Metacognitive myopia: an obstacle to intelligent behavior and lapse of the evolution? - Fiedler, Klaus; Ermark, Florian; Salmen, Karolin (Intelligence, 2022)
In cognitive psychology, those who behave in a particularly rational manner are considered intelligent. First, we briefly introduce the psychology of judgment and decision-making, which has played a key role in theorizing and empirical investigation of cognitive research for decades. We then give an impression of the pessimistic view of the rationality of human behavior that emerged from the research program of the two influential researchers, Daniel Kahneman and Amos Tversky. Yet, Herbert Simon’s idea of bounded rationality provides an often-cited explanation of the many violations of mathematical and logical rules due to “heuristics and biases.” This chapter highlights an alternative explanation that has traditionally received less attention: “metacognitive myopia” is a weakness in the metacognitive monitoring and control function that regulates our thinking. While numerous cognitive fallacies and misjudgments are recurrent and unavoidable, a comprehensive explanation of irrational behavior must also explain why biases and illusions are not detected and corrected at the metacognitive level, despite feedback and education. The uncritical and often naïve adherence to patently non-valid information is the subject of research on metacognitive myopia.
Gesehen am 17.08.2023